Hollow Carbon Sphere and Polyhedral Carbon Composites Supported Iron Nanoparticles as Excellent Bifunctional Electrocatalysts of Zn–Air Battery. Issue 5 (6th March 2022) - Wang, Yuebing; Yi, Ruowei; Chen, Aling; Fang, Can; Wang, Yaping; Yi, Qingfeng; Liu, Meiyang; Liu, Shijie; Zhan, Shaoqi; Zhong, Bin
Abstract : Herein, we synthesize Fe‐based nanocatalysts supported on the composites composed of hollow carbon spheres (HCSs) and metal–organic frameworks (MOFs) by a facile pyrolysis method. The composites with different ratios of HCSs and MOFs present an interesting phenomenon: the oxygen reduction reaction (ORR) limiting current increases along with the HCSs content, while the onset potential and half‐wave potential show the highest values when the ratio between HCSs and MOFs is optimized. The composite catalysts exhibit superior ORR electrocatalytic performance than Pt/C in alkaline and neutral media. Even in the acidic media, these composite catalysts still present a close catalytic activity to Pt/C. For the oxygen evolution reaction (OER) test, the prepared Fe‐NC@NHCS‐600 shows a reduced overpotential to that of the benchmark IrO2 . The rechargeable Zn‐air battery using Fe‐NC@NHCS‐600 as the catalyst of air electrode exhibits superior discharge capability with an open‐circuit voltage of 1.620 V and a maximum power density of 278.97 mW cm −2 in alkaline electrolyte, as well as an open‐circuit voltage of 1.457 V and a maximum power density of 114.96 mW cm −2 in neutral electrolyte. The battery also exhibits steady cycling stability for more than 90 and 70 h at 5 and 10 mA cm −2, respectively. Abstract : The nanocomposites composed of Fe nanoparticles, hollow carbon spheres, metal–organic frameworks, and carbon nanotubes are synthesized and exhibit excellent charge–discharge cycle performance and durability in zinc–air batteries.